Foundations of materials science & engin - Smith/Hashemi. ([S.l.] : Mcgraw-Hill Education, 2005)
"Smith/Hashemi's Foundations of Materials Science and Engineering, 4/e" provides an eminently readable and understandable overview of engineering materials for undergraduate students. Chapters have been updated to reflect new topics such as nanotechnology and biotechnology, and materials types being used in industry. Through concise explanations, numerous worked-out examples, a wealth of illustrations and photos, and a brand new set of online resources, the new edition provides the most student-friendly introduction to the science and engineering of materials. The extensive media package available with the text provides Virtual Labs, tutorials, and animations, among other resources, on the student CD-ROM along with numerous student and instructor resources on the Online Learning Center.